Kemampuan Mahasiswa Mengidentifikasi Kalimat Topik Dalam Bacaan Melalui Pengetahuan Konteks Dan Referensi Pragmatik - Izhar, Izhar; Solikhin, Solikhin (JURNAL PESONA, 2018)
This study aims to improve studentsâ ability in identifying topic sentence in a text through context ability and pragmatic reference. This study is classroom action research. The researcher used test as a research instrumenT. The research procedure was implemented in two cycles adopted from Kemmis model. Each cycle consist of plan, action, observation, and reflection. The result shows that context ability and pragmatic reference can enhance students ability in indentifying topic sentence in a text.